Component-Based microservices for flexible and scalable automation of industrial bioprocesses (2021)
Industry 4.0 involves the digital transformation of the industry with the integration and digitization of all industrial processes that make up the value chain, which is characterized by adaptability, flexibility, and efficiency to meet the needs of customers in today’s market. Therefore, the adaptations of the new bioprocess industry require a lot of flexibility to react quickly and constantly to market changes and to be able to offer more specialized, customized products with high operational efficiency. This paper presents a flexible, scalable, and robust framework based on software components, container technology, microservice concepts, and the publish/subscribe paradigm. This framework allows new components to be added or removed online, without the need for system reconfiguration, while maintaining temporal and functional constraints in industrial automation systems. The main objective of the framework proposed is the use of components based on microservices, allowing easy implementation, scalability, and fast maintenance, without losing or degrading the robustness from previous developments. Finally, the effectiveness of the proposed framework was verified in two case studies (1) a soursop soda making process is presented, with a fuzzy controller implemented to keep the pasteurizer output flow constant (UHT) and (2) an automatic storage tank selection and filling process with actuated valves to direct the fluid to the corresponding tank at the time to start the process. The results showed that the platform provided a high-fidelity design, analysis, and testing environment for the flow of cyber information and its effect on the physical operation in a beverage processing plant with high demand for flexibility, scalability, and robustness of its processes, as they were experimentally verified in a real production process